Genotypic Spectrum in a Cohort of Sri Lankan Patients With Homocystinuria - Hewa Warawitage Dilanthi; Kandana Liyanage Subhashinie Jayasena; Nambage Dona Priyani Dhammika; Neluwa Liyanage Ruwan Indika; Matara Mahavidanage Nishani De Silva; Imalke Kankananarachchi; Pushpa Malkanthi Gardiye Punchihewa; Dharma Irugalbandara; Sabine Schroeder; Kosala Karunaratne; Eresha Jasinge (JIMD Reports)
ABSTRACT Homocystinuria due to cystathionine beta‐synthase (CBS) deficiency is a rare metabolic disorder inherited as an autosomal recessive trait. Spectrum of genetic variants in CBS gene and their correlation with the phenotypes of homocystinuria in Sri Lankan patients have not been reported to date. The objective of this study was to identify the genotypes and genotype–phenotype correlations in a cohort of Sri Lankan patients with homocystinuria due to CBS deficiency. We determined the variants in CBS gene in 14 Sri Lankan patients with homocystinuria, from 9 unrelated families. The clinical features and the biochemical response to pyridoxine were studied for further correlations. Among the 14 patients, the common clinical features were ectopia lentis (100%), intellectual disability (92%) and marfanoid features (78%) at presentation while three of them had developed osteoporosis (21%). Median age at diagnosis was 8 years (range 2–12). Three pathogenic variants (c.1006C>T, c.785C>T and c.19del) and two likely pathogenic variants (c.869C>T, c.772G>A) in CBS gene were identified. Thirteen patients with homozygous genotypes were non‐responsive to pyridoxine while the only patient with the compound heterozygous genotype (c.869C>T/c.772G>A) responded to pyridoxine treatment. The genotypic spectrum observed in Sri Lankan patients is unique and mostly associated with pyridoxine non‐responsiveness. The majority of the patients were identified clinically at a later stage of the disease due to lack of a screening programme in the country. Therefore, it is important to improve the awareness of the disease among the clinicians in the interest of early diagnosis and early commencement of metabolic treatment.